CHRONOTOPE IN THE NOVEL BY E. VODOLAZKIN "AVIATOR" - Regina Fakhrutdinova (Bright Mind Publishing, 2025)
The article examines the chronotope of E. Vodolazkin's novel "Aviator" as a complex artistic construction that combines personal and historical dimensions. The transformation of time and space in the narrative is analyzed, and the methods of representing cultural memory, spiritual renewal, and philosophical understanding of eternity are shown.
Keywords: Chronotope, Vodolazkin